Building/Campus Characteristics and Legionella in Potable Water Systems at Veterans Health Administration Facilities. (October 2020) - Gamage, Shantini; Bender, Alan; Simbartl, Loretta; Roselle, Gary; Kralovic, Stephen; Ambrose, Meredith; Coppin, John David; Jinadatha, Chetan; Decker, Brooke K; DeVries, Aaron; Goto, Michihiko; Rizzo, Vincent; et al.
Abstract : Background: When control mechanisms such as water temperature and biocide level are insufficient, Legionella, the causative bacteria of Legionnaires' disease, can proliferate in water distribution systems in buildings. Guidance and oversight bodies are increasingly prioritizing water safety programs in healthcare facilities to limit Legionella growth. However, ensuring optimal implementation in large buildings is challenging. Much is unknown, and sometimes assumed, about whether building and campus characteristics influence Legionella growth. We used an extensive real-world environmental Legionella data set in the Veterans Health Administration (VHA) healthcare system to examine infrastructure characteristics and Legionella positivity. Methods: VHA medical facilities across the country perform quarterly potable water sampling of healthcare buildings for Legionella detection as part of a comprehensive water safety program. Results are reported to a standardized national database. We did an exploratory univariate analysis of facility-reported Legionella data from routine potable water samples taken in 2015 to 2018, in conjunction with infrastructure characteristics available in a separate national data set. This review examined the following characteristics: building height (number of floors), building age (reported construction year), and campus acreage. Results: The final data set included 201, 936 water samples from 819 buildings. Buildings with 1–5 floors (n = 634) had a Legionella positivity rate of 5.3%, 6–10 floors (n = 104) had a rate of 6.4%, 11–15 floors (n = 36) had a rate of 8.1%, and 16–22 floors (n = 9) had a rate of 8.8%. All rates were significantly different from each other except 11–15 floors and 16–22 floors ( P < .05, χ 2 ). The oldest buildings (1800s) had significantly less ( P < .05, χ 2 ) Legionella positivity than those built between 1900 and 1939 and between 1940 and 1979, but they were no different than the newest buildings (Fig. 1). In newer buildings (1980–2019), all decades had buildings with Legionella positivity (Fig. 1 inset). Campus acreage varied from 3 acres to almost 500 acres. Although significant differences were found in Legionella positivity for different campus sizes, there was no clear trend and campus acreage may not be a suitable proxy for the extent or complexity of water systems feeding buildings. Conclusions: The analysis of this large, real-world data set supports an assumption that taller buildings are more likely to be associated with Legionella detection, perhaps a result of more extensive piping. In contrast, the assumption that newer buildings are less associated with Legionella was not fully supported. These results demonstrate the variability in Legionella positivity in buildings, and they also provide evidence that can inform implementation of water safety programs. Funding: None Disclosures: Chetan Jinadatha, principal Investigator/Co-I: Research: NIH/NINR, AHRQ, NSF principal investigator: Research: Xenex Healthcare Services. Funds provided to institution. Inventor: Methods for organizing the disinfection of one or more items contaminated with biological agents. Owner: Department of Veterans Affairs. Licensed to Xenex Disinfection System, San Antonio, TX.